1996
DOI: 10.1136/jmg.33.9.737
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of psychological functioning one year after the predictive test for Huntington's disease and impact of the test result on reproductive decision making.

Abstract: For people at risk for Huntington's disease, the anxiety and uncertainty about the future may be very burdensome and may be an obstacle to personal decision making about important life issues, for example, procreation. For some at risk persons, this situation is the reason for requesting predictive DNA testing. The aim of this paper is two-fold. First, we want to evaluate whether knowing one's carrier status reduces anxiety and uncertainty and whether it facilitates decision making about procreation. Second, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 21 publications
0
96
0
2
Order By: Relevance
“…8 A new finding is that test motivation also has a strong predictive value with respect to long-term distress, independently of ego-strength and test result.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 A new finding is that test motivation also has a strong predictive value with respect to long-term distress, independently of ego-strength and test result.…”
Section: Discussionmentioning
confidence: 99%
“…29 In our group of tested persons, the ratio female/male in non-carriers proved to be larger than in carriers. 8 Finally, for a discussion of post-test reproductive decisions, we refer to the results of the European collaborative study 30 on reproductive decisions after predictive testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A minority was undecided or had no children for other reasons, such as an unstable relationship. A previous study 23 reported that 1 year after predictive testing one-third of the carriers was still undecided. These findings indicate that some couples need a long time of reflection on reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Reasons for excluding the remaining papers were as follows: 10 were reviews, 17-26 10 were qualitative, [27][28][29][30][31][32][33][34][35][36] seven reported only pre-test measures, [37][38][39][40][41][42][43] two were of respective attitudes towards testing or used unstandardised measures, 44,45 and one did not report outcomes for unaffected participants separately from those affected. 46 One small sample, crosssectional study 47 was also excluded as it was preliminary to larger, prospective studies conducted by the same group.…”
Section: Papers Selected For Reviewmentioning
confidence: 99%